(untitled) (Research, Society and Development, 2020)
The evolution of new management systems in organizations and their introduction in the production processes is transforming the traditional industry, taking it to a new level of organizational development. The Fourth Industrial Revolution and the advent of Industry 4.0, characterized by connectivity, digitalization and high productivity technologies, embody a paradigm shift in which quality management may undergo irreversible changes and possibly need to adapt to meet the new expectations and demands of the an increasingly integrated and competitive market, in which managing large volumes with high complexity will become a common activity. Concerned with this management, the present study addresses one of the aspects of the adequacy of quality management to the new reality, through a qualitative and quantitative research among representatives of the academic environment and industry professionals, on the use and importance of quality tools in the industry. 4.0. The tools that would be most used in industry 4.0 were evaluated, and if there are differences of opinion regarding quality specialists and the general public (academics and industry professionals). It is concluded that there is still much to discuss and improve on the application of quality tools in the vast world 4.0 in the search for greater efficiency and effectiveness of production processes.